2021
DOI: 10.1186/s12891-021-04568-z
|View full text |Cite
|
Sign up to set email alerts
|

Use of iliac screw associated with more correction of lumbar lordosis than S2-alar-iliac screw for adult spinal deformity

Abstract: Background To date, there is a paucity of reports clarifying the change of spinopelvic parameters in patients with adult spinal deformity (ASD) who underwent long segment spinal fusion using iliac screw (IS) and S2-alar-iliac screw (S2AI) fixation. Methods A retrospective review of consecutive patients who underwent deformity correction surgery for ASD between 2013 and 2017 was performed. Patients were divided into two groups based on whether IS or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 48 publications
0
14
1
Order By: Relevance
“…Thus, we postulate that: on the one hand, the patient positioning of slight hip extension during surgery might cause the anterior rotation of the sacrum, resulting in intraoperative increase of PI, which would be nally maintained by the application of sacroiliac xation, on the other hand, incremental stress to SIJ after spinopelvic xation accelerates SIJ degeneration, inducing an increasing motion. In this study, we nd the PI is increased by an average of 4.3° at the nal follow-up, which is smaller than the ndings of Lee et al xation was well-introduced by many authors [19,36,48,49]. The change in PI after S2AI instrumentation may be due to direct xation and modi cation of the SIJ, which have been reported by cadaveric study [50].…”
Section: Discussioncontrasting
confidence: 56%
“…Thus, we postulate that: on the one hand, the patient positioning of slight hip extension during surgery might cause the anterior rotation of the sacrum, resulting in intraoperative increase of PI, which would be nally maintained by the application of sacroiliac xation, on the other hand, incremental stress to SIJ after spinopelvic xation accelerates SIJ degeneration, inducing an increasing motion. In this study, we nd the PI is increased by an average of 4.3° at the nal follow-up, which is smaller than the ndings of Lee et al xation was well-introduced by many authors [19,36,48,49]. The change in PI after S2AI instrumentation may be due to direct xation and modi cation of the SIJ, which have been reported by cadaveric study [50].…”
Section: Discussioncontrasting
confidence: 56%
“…Ishida et al hypothesized that S2AI screws might prevent postoperative increases in PI by rigidly fixing the SI joint. Conversely, Luo et al found a significant change in PI (>5°) in more than 50% of patients treated with IS screws as compared with only 13% of patients with S2AI screws 27 . Finally, other papers showed minimal changes in postoperative PI in patients operated for ASD with lumbo-pelvic fixation 28 .…”
Section: Discussionmentioning
confidence: 96%
“…Conversely, Luo et al found a significant change in PI ( > 5°) in more than 50% of patients treated with IS screws as compared with only 13% of patients with S2AI screws. 27 Finally, other papers showed minimal changes in postoperative PI in patients operated for ASD with lumbo-pelvic fixation. 28 However, these papers only compared mean PI as opposed to the categorization of significant change in PI, which might have diluted the findings.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, a study by Luo et al showed that the use of subcrestal iliac screw fixation is associated with greater correction of lumbar lordosis and a possible increase in pelvic incidence when compared with S2AI screw in patients treated for adult spinal deformity. 28 They described the iliac screw entry point as approximately 10 mm between the posterior edge of the iliac crest and the posterior surface of the sacrum and connected with a lateral connector to the rod below the S1 pedicle screw. Additionally, the screw was deeply inserted, making the screw head flush with the cortex of the iliac bone with the aim of lowering the risk of screw prominence.…”
Section: Modified Subcrestal Iliac Screws Techniquementioning
confidence: 99%